Minimally invasive surgical techniques for the therapy of far lateral disc herniation in middle-aged and elderly patients. (1st October 2019) - Ren, Weijian; Chen, Yu; Xiang, Liangbi
Abstract: To examine the clinical results of different minimally invasive techniques for the therapy of far lateral disc herniation in middle-aged and elderly patients. An endoscopic approach (percutaneous endoscopic lumbar discectomy; PELD), MIS-TLIF combined with contralateral translaminar screw (MIS-TLIF CTS), and MIS-TLIF combined with bilateral pedicle screws (MIS-TLIF BPS) were evaluated via a retrospective chart review. Data from 74 consecutive middle-aged and elderly patients with far lateral disc herniation were analyzed. All patients underwent surgery; 19 with PELD, 24 with MIS-TLIF CTS, and 31 with MIS-TLIF BPS. Clinical data included the length of the incision, duration of the operation, estimated blood loss, hospitalization time, operation cost, recurrence rate, and fusion rate. Preoperative and postoperative patient outcomes including the VAS, ODI scores and MacNab criteria were assessed and recorded. The mean follow-up time was 26.4 months (range from 14 to 46 months). Compared with the internal fixation groups, the length of the incision, duration of operation, estimated blood loss, and hospitalization time were obviously lower in the PELD group. The difference in operation cost among the three methods was statistically significant. The postoperative VAS scores for LBP and LP decreased significantly as compared with those recorded preoperatively. The postoperative ODI scores were lower than those recorded preoperatively. MacNab criteria rating excellent, good and fair results were in 27, 37 and 10 patients, respectively. Conclusion: PELD, MIS-TLIF CTS, and MIS-TLIF BPS are all effective minimally invasive techniques for the therapy of single segment far lateral lumbar disc herniation in middle-aged and elderly patients. PELD had a shorter operation time and less surgical trauma, being a less invasive and more economical method; however, there was no recurrence of disc herniation after fixation. Compared with MIS-TLIF BPS, MIS-TLIF CTS obtained a similar clinical effect and certain costs were saved.